Pengaturan Tindak Kejahatan Judi Online di Internet dalam Perspektif Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Prabu Kemal Manaf (Pusat Riset dan Inovasi Nasional, 2024)
The development of information technology has had positive and negative impacts on society, one of which is the increase in crime in the digital realm, including online gambling. Online gambling has become a serious problem because it can harm various social and economic aspects. Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) exists as a legal instrument that aims to regulate activities in the digital world, including preventing and taking action against online gambling practices. This journal examines the regulations implemented in handling online gambling crimes based on the ITE Law and the challenges faced in implementing them in Indonesia.